Drive Systems for Landing Gears Numerically Simulated in AMESim Software. (28th February 2023) - Dinca, L.; Corcau, J. I.; Vaden, C. V.
Abstract : This work presents two versions of landing gear drives numerically simulated. We follow to obtain the right driving sequence of the legs and doors and the estimation of the landing gear deploy and retract time. Although the studies in this paper do not exhaust all the aspects concerning landing gear hydraulic system functioning, these are useful in the design phase of the aircraft hydraulic systems. Regarding the landing gear hydraulic system, we highlight one version of the drive stall phenomenon. When the hydraulic feeding pressure decreases, it is possible that the forces developed by the hydraulic cylinders are enough to retract completely the legs. The landing gear remains in an intermediate position, and the aircraft cannot accomplish its mission safely. For a second version, logic command functions are synthesized using Karnaugh diagrams, and after that, the numerical simulation is accomplished to validate the solution. We used the AMESim software to perform numerical simulations.